Enhancing the financial sustainability of vulnerable poor group through the implementation of Qard Al-Hasan as i-CSR mechanisms by Islamic banking institutions - Che Man, Norajila; P. Rameli, Mohd Faizal; Wan Jusoh, Wan Noor Hazlina; Lateh, Najahudin (2023)
The term "vulnerable poor" refers to individuals who experience sudden poverty without being adequately prepared to cope with it. This type of poverty can arise from various factors, such as the loss of income due to economic uncertainties stemming from pandemics or disasters. Consequently, there is a pressing need for a sustainable mechanism that addresses this group's social welfare and economic well-being. Establishing a sustainable and comprehensive i-CSR (Islamic Corporate Social Responsibility) mechanism is crucial to achieving these objectives. This initiative aligns with the Value-Based Intermediation (VBI) introduced by Bank Negara to elevate the function and potential of Islamic banking while also supporting the government's goal of eradicating poverty, as outlined in Goal 1 of the Sustainable Development Goals (SDG) for 2030. To ensure financial sustainability for the vulnerable poor, this study was conducted to explore the CSR mechanisms employed in Islamic banking in Malaysia and to assess the potential of the i-CSR mechanism in facilitating financing for the vulnerable poor from Islamic banks. This study adopted the exploratory research method, employing interviews and content analysis of previous studies to gain insights into the concepts of CSR and i-CSR. Authoritative informants were interviewed to obtain their perspectives on CSR and i-CSR-related questions, and the collected data were analysed using content analysis techniques. The findings of this study emphasise that the implementation of a standardised i-CSR mechanism in Islamic banking in Malaysia has the potential to significantly contribute to the attainment of the first agenda of the Sustainable Development Goals 2030 namely eradication of poverty. This can be achieved by addressing poverty in its various forms, particularly by empowering the vulnerable poor through increased access to micro-financing opportunities. This research highlights on Qard alHasan as a mechanism of i-CSR in Islamic bank. Further research can explore other i-CSR mechanisms to be use by Islamic bank such as Waqf to affectively aiding various segment in the society. The proposed model of Qard al-Hasan can be used by Islamic Financial Institutions as a whole in structuring their i-CSR activities. This research contributes to the body of knowledge on improving the financial sustainability of a vulnerable and disadvantaged group through the use of Qard al-Hasan as a mechanism within the framework of Islamic banking institutions.